Role of Class 2 Integron in Antibiotic Susceptibility Pattern of Acinetobacter baumannii Strains Isolated from Hospitals in Tehran - Reza Mirnejad (پزشکی بالینی ابن سینا, 2012)
Introduction & Objective: Acinetobacter baumannii is an important nosocomial pathogen all over the world and has emerged as a threat to public health which also exhibit multiple-antibiotic resistance. Studies of antibiotic resistance mechanism in these bacteria have demonstrated the presence of specific antimicrobial resistance genes located mainly in integrons. The purpose of this study was to search for the presence of the class 2 integron in strains of A. baumannii found in Tehran-Iran and the relationship between the presence of this integron and the antimicrobial susceptibility patterns. Material & Methods: This cross sectional study was performed in three main hospitals in Tehran on 500 clinical samples during a 10 month period (March to December 2010). In laboratory, after identifying the species of A. baumannii by using culture and biochemical methods, disc diffusion method according to CLSI guidelines was performed to determine the sensitivity of 50 isolates of these bacteria to 13 antibiotics. Polymerase chain reaction (PCR) was performed for the detection of integron class 2 by Int2F/R primers. Eventually correlation of multi-drug resistance and existence of integron class II were studied. Results: Of these 500 samples, 50(71.5%) strains of A. baumannii, 12(17%) A. lwoffii strains and 8 (11.5) other Acinetobacter species were isolated. The most common resistance detected among 50 isolates was to Cefepime, Ceftazidime, Aztreonam, Norfloxacin, Ciprofloxacin, Ofloxacin, and Amikacin. Also, less resistance was observed to imipenem, Gentamycin, Ampicillin- sulbactam, Piperacillin-Tazobactam. Meropenem and Tobramycin were considered as effective drugs in this study. Class 2 integrons were found in 41 (82%) of the 50 isolates of A. baumannii. Moreover, a significant correlation between integron class2 and resistance to antibiotics of Cefepime, Ceftazidime, Aztreonam, Norfloxacin, Ciprofloxacin, Ofloxacin, and Amikacin were observed. Conclusion: Our findings indicates that class 2 integron are widely spreads among A. baumannii isolated in Tehran, Iran and plays an important role in multidrug resistance in these bacteria. Therefore, monitoring drug resistance due to integron class 2 by PCR, in protocols of infection control due to multidrug-resistant A. baumannii in hospitals of Tehran is important.